Good soil management can reduce dietary zinc deficiency in Zimbabwe - Muneta G. Manzeke-Kangara; Edward J. M. Joy; Florence Mtambanengwe; Prosper Chopera; Michael J. Watts; Martin R. Broadley; Paul Mapfumo (CABI Agriculture and Bioscience)
Abstract Background Dietary zinc (Zn) deficiency is widespread in sub-Saharan Africa (SSA) with adverse impacts on human health. Agronomic biofortification with Zn fertilizers and improved soil fertility management, using mineral and organic nutrient resources, has previously been shown to increase Zn concentration of staple grain crops, including maize. Here, we show the potential of different soil fertility management options on maize crops to reduce dietary Zn deficiency in Zimbabwe using secondary data from a set of surveys and field experiments. Methods An ex-ante approach was used, informed by published evidence from studies in three contrasting smallholder production systems in Zimbabwe. To estimate current Zn deficiency in Zimbabwe, data on dietary Zn supply from non-maize sources from the Global Expanded Nutrient Supply (GENuS) data set were linked to maize grain Zn composition observed under typical current soil fertility management scenarios. Results A baseline dietary Zn deficiency prevalence of 68% was estimated from a reference maize grain Zn composition value of 16.6 mg kg−1 and an estimated dietary Zn intake of 9.3 mg capita−1 day−1 from all food sources. The potential health benefits of reducing Zn deficiency using different soil fertility management scenarios were quantified within a Disability Adjusted Life Years (DALYs) framework. A scenario using optimal mineral NPK fertilizers and locally available organic nutrient resources (i.e. cattle manure and woodland leaf litter), but without additional soil Zn fertilizer applications, is estimated to increase maize grain Zn concentration to 19.3 mg kg−1. This would reduce the estimated prevalence of dietary Zn deficiency to 55%, potentially saving 2238 DALYs year−1. Universal adoption of optimal fertilizers, to include soil Zn applications and locally available organic leaf litter, is estimated to increase maize grain Zn concentration to 32.4 mg kg−1 and reduce dietary Zn deficiency to 16.7%, potentially saving 9119 DALYs year−1. Potential monetized yield gains from adopting improved soil fertility management range from 49- to 158-fold larger than the potential reduction in DALYs, if the latter are monetized using standard methods. Conclusion Farmers should be incentivized to adopt improved soil fertility management to improve both crop yield and quality.